Mufaro's beautiful daughters an African tale - Steptoe, John 1950- (London Puffin Books, 1997)
Mufaro's two beautiful daughters, one bad-tempered, one kind and sweet, go before the king, who is choosing a wife.
Keywords: Fairy tales; Africa -- Fiction